2006
DOI: 10.2165/00019053-200624070-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Lung Cancer

Abstract: Cost of illness (COI) studies estimate the overall economic burden of a specific disease, rather than simply treatment-related costs. While having been criticised for not allowing resource prioritisation, COI studies can provide useful guidance, so long as they adhere to accepted methodology. The aim of this review is to analyse the methods used to evaluate the cost of lung cancer. Because of the increasing incidence and high direct and indirect costs of lung cancer, it is an important disease in terms of econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Notably, in the current study indirect costs (68.6%) were the major cost driver for the total economic burden of lung cancer, while direct costs accounted only for 31.4% of total disease burden. Similarly, in a methodologic review on cost of lung cancer, the authors considered lung cancer to be a costly illness with hospitalization and treatments accounting for a large part of direct costs, while the indirect costs represent a large part of the total costs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in the current study indirect costs (68.6%) were the major cost driver for the total economic burden of lung cancer, while direct costs accounted only for 31.4% of total disease burden. Similarly, in a methodologic review on cost of lung cancer, the authors considered lung cancer to be a costly illness with hospitalization and treatments accounting for a large part of direct costs, while the indirect costs represent a large part of the total costs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In European countries, the total burden of lung cancer was estimated to be €106.4 billion with direct costs accounted for €3.35 billion of the total cost and indirect costs related to disability and premature mortality accounted for €100 billion and per patient direct cost of €11,473 [ 4 , 6 ]. Other studies also revealed the hospitalization, mortality and indirect costs to account for the largest part of the direct, indirect and total costs for lung cancer, respectively [ 6 , 15 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the productivity loss for patients and their families beyond this age range were not considered in this study. Since the lost wages were considered over five years, a 3% inflation index was used to convert past monetary values into present value in 2014 [6,30]. The Medical Ethics Committee of Harbin Medical University (Daqing) agreed with this study and examined the project for related medical ethics problems.…”
Section: Methodsmentioning
confidence: 99%
“…As the population ages, the expenditure for lung cancer treatment will become even more burdensome to the entire society [4,5,6]. To date, a relatively large amount of research has been done on the economic burden of lung cancer worldwide [7,8,9,10,11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, nuclear energy is used in 30 countries [3] and holds the potential to reduce not only dependence on fossil fuel-based energy sources but also undesirable emissions of greenhouse gases (GHGs) and precursor pollutants from photochemical oxidants and secondary aerosols, thereby contributing to climate change mitigation and reducing harmful effects on human health [4][5][6][7][8][9]. In comparison with other available low-carbon technologies, such as solar and wind, some advantages of nuclear energy are its high energy density through the occupation of smaller installed areas for the production of the same amount of energy [10][11][12] and its continued availability, providing energy security regardless of external factors such as environmental conditions and the amount of available reserves [13,14].…”
Section: Introductionmentioning
confidence: 99%